2005
DOI: 10.1097/01.ju.0000165159.33772.5b
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogen, Vaccine and Combination Therapy in Patients With Nonmetastatic Hormone Refractory Prostate Cancer

Abstract: Further studies are merited to investigate the role of combining vaccine with antiandrogen therapy or vaccine followed by vaccine plus antiandrogen therapy in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 15 publications
0
66
0
Order By: Relevance
“…Median time on study with the combined therapy was 5.2 months, with a total duration from onset of study of 15.9 months. Both vaccine and nilutamide appeared to have clinical activity, but patients appeared to respond better to nilutamide after receiving vaccine This study was the first to provide preliminary evidence that the combination of vaccine and hormone therapy may have more clinical benefit than either modality alone [49]. A followup analysis of this study showed that the 5-year survival rate was 75% for patients who received vaccine first then had nilutamide added, compared to a 43% 5-year survival rate for patients who started on nilutamide then had vaccine added [50].…”
Section: Vaccine and Androgen-deprivation Therapymentioning
confidence: 83%
See 1 more Smart Citation
“…Median time on study with the combined therapy was 5.2 months, with a total duration from onset of study of 15.9 months. Both vaccine and nilutamide appeared to have clinical activity, but patients appeared to respond better to nilutamide after receiving vaccine This study was the first to provide preliminary evidence that the combination of vaccine and hormone therapy may have more clinical benefit than either modality alone [49]. A followup analysis of this study showed that the 5-year survival rate was 75% for patients who received vaccine first then had nilutamide added, compared to a 43% 5-year survival rate for patients who started on nilutamide then had vaccine added [50].…”
Section: Vaccine and Androgen-deprivation Therapymentioning
confidence: 83%
“…A phase II clinical trial in this patient population employed rV-PSA plus rV-B7-1 followed by rFPSA boosting [49]. Patients who were not surgically castrate remained on ADT and were randomized to vaccine (n = 21) versus ARA therapy with nilutamide (n = 21).…”
Section: Vaccine and Androgen-deprivation Therapymentioning
confidence: 99%
“…A phase II clinical trial in patients with D0.5 prostate cancer employed rV-PSA plus rV-B7-1 followed by rF-PSA boosting. 35 Patients who were not surgically castrate remained on ADT and were randomized to vaccine (n = 21) versus androgen-receptor antagonist (ARA) therapy with nilutamide (n = 21). After 6 months, patients with rising PSA and no metastasis could receive a combination of both treatments.…”
Section: Vaccine Plus Hormone Therapymentioning
confidence: 99%
“…There is increasing evidence that patients who have some form of immunotherapy are more susceptible to responses from radiotherapy, endocrine therapy and chemotherapy. In addition, there is recent evidence to suggest that the sequentiality of these approaches is very important: a study by Arlen and colleagues demonstrated that administering a vaccine for prostate cancer followed by endocrine treatment is significantly more effective than the reverse (endocrine treatment followed by vaccine treatment) [8]. This has major implications for analysis of many ongoing vaccine trials.…”
mentioning
confidence: 99%
“…Although the primary end points of these studies were not reached in randomized studies, a secondary end point of survival (probably more important) has recently been achieved in these studies, specifically combining two randomized studies, and an application for FDA approval has been made [102]. Other approaches have also produced very encouraging data, including the use of whole-cell vaccines from Onyvax (London, UK) in a Phase II study [7], whereby the reduction in the rate of rise of PSA velocity correlated with time-to-disease progression, as well as PSA responses, using a virus-based vector incorporating PSA antigens from Therion (MA, USA) [8]. These data strongly suggest that prostate cancer may be a much better target than melanoma.…”
mentioning
confidence: 99%